Predicting the network throughput of wide area WSN in rural areas - Murdiyat, P.; Chung, Kah-Seng; Chan, King-Sun (Institute of Electrical and Electronics Engineers Inc., 2015)
Multi-hop wireless sensor networks (WSN) have many applications in nowadays' environment monitoring. However, it is very challenging to predict the throughput for an arbitrary multi-hop wireless sensor network with different source data rates. In this paper, we propose an iterative decomposition method for this purpose. We first identify a limited number of basic network configuration of chain topology and determine their respective throughputs through simulation. Then we iteratively decompose the target network configuration into segments, each of which is represented by one of the basic network configurations, to estimate its overall throughput performance. To verify the accuracy of our method, we conduct several simulations in ns-3. Simulation results show that our method is quite accurate and yet very simple.